Production and characterization of galactose oxidase produced by four isolates of Fusarium graminearum - Gasparotto,Elainy Patrícia Lino (2006)
A screening aimed to find new galactose oxidase producer isolates and to evaluate the production among Fusarium graminearum strains was conducted. Thirty-five isolates out of 39 analysed produced the enzyme at several levels. The data indicated a wide distribution of galactose oxidase within F. graminearum and also revealed new producer isolates. The enzyme produced by different isolates showed similar thermal activity and stability and were active on same substrates. However, the optimum pH ranged from 7.0 to 7.5. Thus, all evaluated isolates were suitable for the production of galactose oxidase.